Poczucie własnej skuteczności studentów w rozwijaniu sprawności pisania w języku obcym - Sujecka-Zając, Jolanta (Neofilolog, 2024)
Self-efficacy is a well-known and researched concept originating from the social-cognitive theory of Albert Bandura (1977, 1997). However, it still seems to be able to promote interesting reflections that are important for language education in higher education, both in teacher and learner activities. According to a number of studies learners acquire important skills and attitudes that are linked to a high degree of self-efficacy: they are highly motivated to learn, set ambitious goals for themselves, and are more persistent and committed to learning than those with a low degree of self-efficacy. The text analyses the results of a quantitative-qualitative study conducted among students participating in foreign language classes at the University of Warsaw. The collected data is analysed with the aim of answering the following research questions: What is the level of self-efficacy in written expression in a foreign language at B2-C2 levels? How do the students perceive the teacher-lecturer’s actions to strengthen their sense of self-efficacy? Do they see strengthening their involvement in written expression as a key element of self-efficacy? In addition, we are also interested in their opinion towards the possibilities of Chat GPT in this regard. The results are used to propose some teaching activities that will enhance students’ self-efficacy in written expression at B2-C2 levels as an important motivational factor which may result in a sense of agency.